EFFECTIVENESS OF SAND PLAY THERAPY IN REDUCING EMOTIONAL DISORDERS IN CHILDREN - Ifalahma, Darah; Yuliana, Ana; da Costa Fernandes, Angelina; Margaretha Xan Xao, Maria; Nurul Istiqomah, Risma (LPPM Universitas Duta Bangsa Surakarta, 2025)
Emotional disorders in children, including anxiety, depression, and behavioral dysregulation, can significantly impact their development and well-being. This study investigates the effectiveness of Sand Play Therapy as a nonverbal, child-centered intervention for reducing emotional disorders. Using a quasi-experimental design, 20 children aged 5–6 years were assigned to either an experimental group receiving Sand Play Therapy or a control group. Emotional symptoms were measured using the Emotional Behavior Problems Questionnaire before and after a four week intervention. Results showed the pre-post test scores between groups were significantly different (F(1,37) = 21.78, p < 0.001), confirming the effectiveness of the intervention. Its mean a statistically significant reduction in emotional disorder scores among children who received therapy, supporting the efficacy of Sand Play Therapy in promoting emotional healing. These findings suggest that Sand Play Therapy is a valuable therapeutic tool, particularly for children who struggle with verbal expression.